2019
DOI: 10.1111/iej.13182
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of studies on cyclic fatigue resistance of engine‐driven endodontic instruments

Abstract: The endodontic literature contains a plethora of studies on static and dynamic cyclic fatigue resistance tests performed on a large array of rotary or reciprocating nickel–titanium endodontic instruments. It was the aim of this review to summarize the currently available evidence to point out the different outcomes from static versus dynamic tests and to assess whether cyclic fatigue tests provide useful data and information for clinical practice. An electronic literature research in the database PubMed was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
98
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 111 publications
(153 reference statements)
4
98
0
5
Order By: Relevance
“…Hülsmann et al (2019) reported similar findings to ours and highlighted the differences between static and dynamic cyclic fatigue tests [30]. Nevertheless, only 12% of published cyclic fatigue studies have used a dynamic fatigue device [30]. Most studies that have compared static and dynamic cyclic fatigue studies have concluded that the time to fracture of endodontic rotary instruments submitted to dynamic cyclic fatigue studies was approximately 20-40% higher than that found in static cyclic fatigue studies [26,[31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Hülsmann et al (2019) reported similar findings to ours and highlighted the differences between static and dynamic cyclic fatigue tests [30]. Nevertheless, only 12% of published cyclic fatigue studies have used a dynamic fatigue device [30]. Most studies that have compared static and dynamic cyclic fatigue studies have concluded that the time to fracture of endodontic rotary instruments submitted to dynamic cyclic fatigue studies was approximately 20-40% higher than that found in static cyclic fatigue studies [26,[31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 73%
“…Ray et al (2007) also performed dynamic cyclic fatigue studies with standardized axial movement, and they concluded that the pecking motion increased the lifespan of the endodontic rotary instruments submitted to cyclic fatigue compared with the results obtained from static cyclic fatigue studies [29]. Hülsmann et al (2019) reported similar findings to ours and highlighted the differences between static and dynamic cyclic fatigue tests [30]. Nevertheless, only 12% of published cyclic fatigue studies have used a dynamic fatigue device [30].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been concluded that cyclic fatigue resistance of the NiTi endodontic instruments highly depends on the alloy, cross-sectional design and the manufacturing method [28,29]. The extensive testing of the cyclic fatigue of newly developed instruments has a significant clinical importance [4].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous editorial, it was suggested that it should be the responsibility of the manufacturers to provide relevant data (Hülsmann ). Secondly, as demonstrated in a review paper in this issue of the IEJ (Hülsmann et al ), the results from studies on cyclic fatigue – static or dynamic in nature – vary considerably. There are differences up to more than 100% between dynamic and static tests, and even the results between static tests differ significantly.…”
mentioning
confidence: 99%